Effectiveness of Midwife-Led Support in Improving Exclusive Breastfeeding Success among Breastfeeding Mothers - Nur Ekawati; Nelly Nugrawati (Jurnal Ilmu Kesehatan Nusantara, 2026)
Background: Exclusive breastfeeding provides essential nutrition and immunological protection during the first six months of life. However, many mothers discontinue breastfeeding because of limited knowledge, low self-confidence, lactation difficulties, family pressure, and work-related barriers. Continuous support from midwives may improve breastfeeding success. Research Objective: This study aimed to determine the effectiveness of midwife-led support in improving exclusive breastfeeding success among breastfeeding mothers in Makassar. Methods: A quasi-experimental study with a non-equivalent control group was conducted from January to July 2025. Seventy-two breastfeeding mothers were recruited through consecutive sampling and allocated to intervention and control groups, with 36 participants in each group. The intervention included counselling, practical breastfeeding assistance, family involvement, scheduled follow-up, digital communication, and return-to-work preparation for six months. The control group received routine maternal and child health services. Data were analysed using descriptive statistics, the chi-square test, comparative tests, and multivariable logistic regression. Results: Six-month exclusive breastfeeding success was significantly higher in the intervention group than in the control group (77.8% versus 50.0%; p=0.014). Midwife-led support increased breastfeeding knowledge and self-efficacy and reduced positioning problems, nipple pain, perceived insufficient milk, and early formula introduction. Mothers receiving the intervention had 3.82 times greater adjusted odds of exclusive breastfeeding success (95% CI: 1.31–11.13). Conclusion: Structured and continuous midwife-led support effectively improved complete six-month exclusive breastfeeding. Its integration into routine maternal and child health services is recommended.